An economic model of the distribution of family income in Canada - Charles M. Beach; Aidan Worswick (Queen's University, Department of Economics, 2019)
This paper develops an economic model of the distribution of income based on shares of family incomes in Canada over 1976-2016. Major determinants of quintile and decile shares of total and market income include male and female participation rates, unemployment rate, inflation rate, GDP growth rate and manufacturing-to-services employment ratio. The analysis tests the hypothesis of GDP growth neutrality ("a rising tide lifts all boats") and strongly rejects it. It also examines the distributional benefits and losses from automation and globalization, and finds significant effects of both over the middle and upper two quintile shares, but mixed effects over the lower two quintiles.
Keywords: D30; D31; J01; J30; 330; income share model; family income distribution; Canadian income distribution